Advancement of the Oxidized State of an As-Cast Low-Mn, High-Cr Cantor’s Alloy in Natural Air at 1000 °C - Lyna Amrouche; Patrice Berthod (Corrosion and Materials Degradation)
In order to discover how the multiple oxides observed in the final external scales after long exposure of a low-Mn, high-Cr Cantor’s alloy to hot air were formed, oxidation tests in a furnace were performed for seven different durations. Metallographic characterization was carried out concerning the oxidation products obtained after each test duration. The different oxides did not appear one after the other, but simultaneously, early on in the exposure to hot air and after. They all thickened progressively and the chemical composition of each also evolved with time, more or less. Globally, the innermost oxide is almost entirely chromia, much richer in Cr than in Mn, while the outermost one contains principally Mn. The interrupted tests also allowed specifying the mass gain kinetic, which is parabolic and twice as fast as a chromia-forming alloy. Despite the lowered content in Mn, manganese still plays an important role in the oxidation phenomenon, starting very early.